2016
DOI: 10.3389/fmicb.2016.01732
|View full text |Cite
|
Sign up to set email alerts
|

E. coli Surface Properties Differ between Stream Water and Sediment Environments

Abstract: The importance of E. coli as an indicator organism in fresh water has led to numerous studies focusing on cell properties and transport behavior. However, previous studies have been unable to assess if differences in E. coli cell surface properties and genomic variation are associated with different environmental habitats. In this study, we investigated the variation in characteristics of E. coli obtained from stream water and stream bottom sediments. Cell properties were measured for 77 genomically different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 55 publications
(61 reference statements)
3
40
0
2
Order By: Relevance
“…Contrastingly, measurement of the cell surface hydrophobicity reflects the abundance and type of proteins and sugars on the cell surface, distinct from the membrane lipid distribution and associated fluidity (47). The environmental isolates used in this study are part of a larger set that was previously characterized in terms of various cell surface properties, including hydrophobicity (41). Hydrophobicity was found to range from 1 to 90% adhesion to hydrocarbons (41).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrastingly, measurement of the cell surface hydrophobicity reflects the abundance and type of proteins and sugars on the cell surface, distinct from the membrane lipid distribution and associated fluidity (47). The environmental isolates used in this study are part of a larger set that was previously characterized in terms of various cell surface properties, including hydrophobicity (41). Hydrophobicity was found to range from 1 to 90% adhesion to hydrocarbons (41).…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been demonstrated that short-chain fatty acids are inhibitory to E. coli, having a detrimental impact on both growth and fatty acid production (9,18,42). Several E. coli strains were previously isolated from Squaw Creek in Ames, IA, and characterized in terms of various cell surface properties and phylotype (Table 1) (41). Given that these environmental isolates have previously demonstrated an ability to survive and propagate under harsh environmental conditions, we proposed that these environmental isolates may be able to provide insight into design strategies for developing robust microbial cell factories for short-chain fatty acid production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These E. coli isolates were of different genotype according to our previous repetitive sequence based-PCR (rep-PCR) and fingerprint profile analysis, using a maximum similarity cut-off of 90% (Liang et al, 2016). The E. coli lab strain MG1655 was used as a K12 control.…”
Section: Methodsmentioning
confidence: 99%